Diseño de un sistema integral de gestión de medicamentos. (2022)
Non trasmitible diseases, also known as chronic diseases, are conditions that last from one year to a lifetime that can require medication to avoid the diseas to advance and for the paciente to have a better life quality. The ideal situation would be that the pacients took all their medications, in the right ammount, time and concentration, that is what is called “adherence” to the farmacological treatments and is a factor that is very important for the treatment to work and really mantaine or improve the pacient´s health; but the reallity is far from that and a lot of poeple is not adherent, because they forget at the moment, they do not buy the medication, or any other reason. This Project aims to adress this problem, to help people to remember their dose, manage their medications and keep track of their process, to improve the adherence.